25 years of its creation: comments on the relationship between Indecopi and the judicial power In the framework of insolvency proceeding - Agurto Isla, Renzo (2017)
The insolvency system in Peru, besides having a private nature, has a sui generis administrative nature governed by the Insolvency Law, hence being supervised by the Indecopi. It is so that the later and the Judicial Power have a constant relationship that, if not properly regulated and developed, can cause negative consequences and disincentives on privats.The author develops the aforementioned relationship through a historical account and, a development of the elements of its interaction. He focuses on the administrative litigation process and on its main basis, the right to effective judicial protection. On the other hand, it raises options of “temporary” solution to the determined challenges, due to the sui generis administrative nature of this system, to generate transparency and predictability in it.